(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the Role of lateral internal sphincterotomy versus conservative management with glyceryl trinitrate in anal fissure in relieving the symptoms Study Design: It is an experimental study. Place & Duration of Study: This study was carried out in surgical unit of Fuji Foundation Hospital Lahore from September 2014-November, 2016. Methods: A Total of 100 patients were included in this study reported with pain in the perianal area with or without bleeding per rectum with no co-morbidities or other systemic illness. Their age ranges between 20 to 60 years. Patients were examined and divided into two equal groups (A and B) containing 50 patients each. Group A underwent conservative management (glyceryl trinitrate) while group B underwent lateral internal sphincterotomy. Results: A total of 100 patients were included in this study, including 87% females and 13%e males. The highest prevalence of anal fissure was seen in the 40–59 years of age group and it was more prevalent in female patients. The ratio of female to male was 4:1. In Group B, 74% patients showed immediate response after the surgery and their symptoms improved while passing stools. Glyceryl trinitrate is not effective in younger age group at the same time lateral internal sphincterotomy is not a procedure of choice in older age group as 2% of patients developed flatus incontinence. Similarly, patients of younger age group did not respond to glyceryl trinitrate at all, rather they requested sphincterotomy to be undertaken. Conclusion: Lateral internal sphincteroyomy is superior method for relieving symptoms of painful defecation for longer period of time as compared to other non-interventional methods.